Manfaat Konsumsi Buah Dan Sayur Untuk Penderita Diabetes Mellitus - Dwi Mayasari (An-Najat, 2023)
Background: Perkeni (2015) revealed that the high accumulation of fat in the body can cause insulin resistance which will then affect glucose levels in the blood. Kumar et al, (2014) explained that daily consumption of Sugar-Sweetened Beverages (SSBs) is related to the incidence of Diabetes Mellitus (DM). Excessive consumption of Sugar-Sweetened Beverages (SSBs) in the elderly can increase the risk of Diabetes Mellitus (DM) because it can cause sugar to accumulate in the blood (hyperglycemia) due to the risk of impaired carbohydrate metabolism in the elderly. The results of Ramadhani's research (2018) show that people who consume high sugar intake have a 9.375 times the risk of suffering from Diabetes Mellitus (DM) compared to people who consume low sugar intake.